ANALISIS SOVEREIGN RISK DI NEGARA-NEGARA ASEAN - Irene Kristiani Tampubolon (Departemen Ekonomi Pembangunan USU, 2013)
The purpose of this research was to test the effect of macro-economic indicators as explanatory variables sovereign risk premium to credit default swaps in ASEAN countries. The variables that used in this research is economic growth, inflation, government debt, foreign exchange reserves, fiscal deficit, current account deficit as independent variables and credit default swaps as the dependent variable. A panel dataset consisting of five ASEAN countries in the period 2007-2011 (annual frequency) is used to verify the pattern of relationships that exist.The results of research showed that inflation and current account deficits had positive influence and statistically significant to credit default swaps. The variables that influence government debt is positive but not statistically significant. Economic growth, foreign exchange reserves and fiscal deficit had negative influence and insignificant influence to credit default swaps ASEAN countries in the period 2007-2011.Keywords : Sovereign Risk, Credit Default Swap, Macroeconomic Fundamen-tal, Panel Data